Detection of SARS-CoV-2 in Milk From COVID-19 Positive Mothers and Follow-Up of Their Infants - Bertino, Enrico; Moro, Guido Eugenio; De Renzi, Giuseppe; Viberti, Giuseppina; Cavallo, Rossana; Coscia, Alessandra; Rubino, Carlotta; Tonetto, Paola; Sottemano, Stefano; Campagnoli, Maria Francesca; Soldi, Antonella; Mostert, Michael; et al. (Frontiers in Pediatrics, 2020)
Aim: In the current SARS-Coronavirus-2 (SARS-CoV-2) pandemic, little is known about SARS-CoV-2 in human milk. It is important to discover if breast milk is a vehicle of infection. Methods: This is a prospective collaborative observational study where samples of human milk from 14 breastfeeding mothers positive for SARS-CoV-2 were collected. A search of viral RNA in breast milk samples was performed by rt-PCR methodology tested for human milk. All the newborns underwent a clinical follow up during the first month of life or until the finding of two sequential negative swabs. Results: In thirteen cases the search for SARS-CoV-2 RNA in milk samples resulted negative and in one case it was positive. Thirteen of the fourteen newborns were exclusively breastfed and closely monitored in the first month of life. Clinical outcome was uneventful. Four newborns tested positive for SARS-CoV-2 and were all detected in the first 48 hours of life, after the onset of maternal symptoms. Also the clinical course of these 4 infants, including the one who received mother’s milk positive for SARS-CoV-2, was uneventful, and all of them became SARS-CoV-2 negative within 6 weeks of life. Conclusion: Our study supports the view that SARS-CoV-2 positive mothers do not expose their newborns to an additional risk of infection by breastfeeding.